Analisis Perwatakan Tokoh Cerpen "Ros Menemukan Suaminya" Karya Diani Savitri - Albertina Rosdina Pero; Namang, Katharina Woli (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This study aims to determine the character in the short rose's character finding her husband. The method used is qualitative. The data source from this study are from Dian Savitri's short story. The data analyzed in this study are sentence words. Paragraph, or quote related to the character's character in the short story of Dian Savitri. Data collection techniques are reading and observing Dian Savitri's short stories, and drawing conclusions. The result of this analysis shows that in the short story contains a character like antagonist and the protagonist.